Art therapy in cancer fight - Érica Rodrigues D'Alencar; Ângela Maria Alves e Souza; Thábyta Silva de Araújo; Francisca de Melo Beserra; Marta Maria Rodrigues Lima; Andreia Farias Gomes (Rev Rene)
Art therapy is the therapeutic use of artistic activity in the context of the professional relationship with people affected by disease, injury or by seeking personal development. This study aims to report the experience of art therapy activities with a group of patients and their caregivers in a university hospital. This is an experience report, in Fortaleza - CE, during September 2010 to February 2011. In the meetings, participated 49 people, who performed activities, using the methods of art therapy, like painting, cutting, drawing, collage, creative visualization and color therapy. In the assessments, after the groups, the participants demonstrated the effects of art therapy, which described that the intervention allowed speak from the process of facing life to cancer fight. It is concluded that the techniques of art therapy provided self-knowledge, self-esteem and redemption sense of well-being with relaxation, and promote happiness and reduce stress.